Comparative analysis of reactor coolant pump coastdown transient using VVER-1200 NPP simulator - Le, Dai Dien (Nuclear Science and Technology, 2017)
Verification has been performed to check the VVER-1200 NPP simulator installed at Nuclear training Center, VINATOM by comparing main parameters in nominal power operation with design data given in safety analysis report of VVER-1200/V392M as well as Ninh Thuan FSSAR. A good agreement was found between the VVER-1200 NPP simulator and VVER-1200/V392M. In this study, the reactor coolant coastdown transient is investigated using the VVER-1200 NPP simulator in comparison with SAR documents. The real time feature of the simulator as well as simulated results performed in the simulator through switching off one reactor coolant pump in comparison with VVER- 1000 experiments are given. A good agreement between the measured and simulated results shows that the thermal hydraulic characteristics and the control protection systems are modeled in a reasonable way. The analysis gives a good basis for the further studies on the simulator.